2005
DOI: 10.1176/jnp.17.3.417
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Taking on Tests Sensitive to Ventromedial Prefrontal Cortex Dysfunction Predicts Early Relapse in Alcohol Dependency: A Pilot Study

Abstract: Twenty one patients in a residential rehabilitation program fulfilling International Classification of Diseases-10 (ICD) criteria for alcohol dependence syndrome were recruited. On neuropsychological tests, alcohol dependent patients relapsed early if they made choices governed by immediate gain irrespective of later outcome, which is consistent with dysfunctional ventromedial-prefrontal cortex mediating the inability to resist the impulse to drink despite ultimately deleterious effects. The authors suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(73 citation statements)
references
References 15 publications
5
65
1
2
Order By: Relevance
“…Thus, disadvantageous decision-making strategies in the Card Playing Task seem to be a vulnerability factor involved in development as well as in relapse of PG. The finding that neurocognitive disinhibition is predictive of relapse is consistent with studies indicating that impairments in self-regulatory neurocognitive functions influence relapse in substance dependence (Tapert et al 1999 ;Allsop et al 2000 ;Bowden-Jones et al 2005). Not all of the neurocognitive variables predicted relapse : a measure of prepotent response inhibition predicted relapse, whereas the Stroop Interference score did not.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Thus, disadvantageous decision-making strategies in the Card Playing Task seem to be a vulnerability factor involved in development as well as in relapse of PG. The finding that neurocognitive disinhibition is predictive of relapse is consistent with studies indicating that impairments in self-regulatory neurocognitive functions influence relapse in substance dependence (Tapert et al 1999 ;Allsop et al 2000 ;Bowden-Jones et al 2005). Not all of the neurocognitive variables predicted relapse : a measure of prepotent response inhibition predicted relapse, whereas the Stroop Interference score did not.…”
Section: Discussionsupporting
confidence: 84%
“…Higher levels of selfreported impulsivity are also found to be predictive of relapse and early treatment drop-out in substance dependence (Moeller et al 2001 ;Doran et al 2004). Other studies in substance-dependent populations indicate that deficiencies in neurocognitive functions have a negative effect on the outcome of interventions such as early drop-out (Teichner et al 2002 ;Aharonovich et al 2003), shorter length of treatment adherence (Fals-Stewart & Schafer, 1992 ;Fals-Stewart, 1993), smaller benefits of treatment interventions (Smith & McCrady, 1991 ;Teichner et al 2001), and higher relapse rates (Tapert et al 1999 ;Allsop et al 2000 ;Bowden-Jones et al 2005). A recent fMRI study indicated that relapse in a group of metamphetaminedependent patients was associated with less activation in the dorsolateral prefrontal cortex, temporal cortex, as well as less activation in the anterior cingulate cortex, brain areas important for functions such as inhibitory control and decision-making processes (Paulus et al 2005).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Bowden-Jones et al (2005) demonstrated that decision-making deficits (e.g., the inability to inhibit the selection of immediately rewarding stimuli associated with poorer outcomes over the longer term) predicted those alcohol-dependent patients would relapse, after completing a 21-day inpatient program, in the following 3 months. Passetti et al (2008) have recently demonstrated a similar relationship using performance on the Cambridge Gamble Task and the Iowa Gambling Task to predict relapse rates in dependent opiate users.…”
Section: Attentional Bias For Drug-related Stimulimentioning
confidence: 99%
“…First, functional magnetic resonance imaging demonstrated impairment of ventromedial prefrontal cortex functioning, an area of the brain thought to be critical in risk processing (Potenza, 2008). Second, various neuropsychological data support faulty risk evaluation and persistence with gambling in the face of adverse consequences (Bowden-Jones et al 2005;Goudriaan et al 2006;Lawrence et al 2009). The reclassification of gambling addiction in DSM 5 as an addictive disorder further strengthens calls on the current Government to modernise gambling legislation, alongside alcohol and drug legislation.…”
Section: Gambling Disordermentioning
confidence: 99%